Periodontal status and salivary flow rate among diagnostic radiology department workers - Alhusaini, Ghadah N.; Mohammed, Ahlam T (Journal of Baghdad College of Dentistry, 2019)
Background: diagnostic radiology field workers are at elevated risk level for systemic and oral diseases like periodontal diseases. This study was aimed to estimate the periodontal condition and salivary flow rate among diagnostic radiology workers. Material and method: The sample for this study consisted of a study group radiographers (forty subjects) working for 5 years at least and control group consisted of nurses and laboratory workers away from radiation (forty subjects) in Baghdad hospitals. All the 80 subjects aged 30-40 year-old and looking healthy without systemic diseases. Plaque, gingival, periodontal pocket depth and clinical attachment loss indices were used for recording the periodontal conditions. Under standardized conditions, collection of unstimulated salivary samples was done and salivary flow rate was measured. Results: Although not significant statistically (p>0.01), analysis of the present study data showed that plaque and gingival indices were higher among radiographers. While periodontal pocket depth and clinical attachment loss were higher among radiographers than control group with statistically highly significant difference (p